Studies on Antarctic fungi. - Onofri Silvano; Zucconi Laura; Selbman Laura; Fenice Massimigliano; Barreca D.; Ruisi S.; TOSI, SOLVEIG (CNR Institute of Atmorpheric PollutionPolarnet Coordinating Unit, 2005)
Research carried out during the last 18 years and still in progress are summarized. They concern investigations on fungal diversity, adaptations, eco-physiological characterization and molecular studies. The main topics of future research are also outlined